Novel Enantiopure Sigma Receptor Modulators: Quick (Semi-)Preparative Chiral Resolution via HPLC and Absolute Configuration Assignment - Marta Rui (Molecules, 2016)
The identification of novel pan-sigma receptor (SR) modulators, potentially useful in cancer treatment, represents a new goal of our research. Here, we report on the preparation of novel chiral compounds characterized by a 3-C alkyl chain bridging an aromatic portion to a 4-benzyl-piperidine moiety. All of the studied compounds have been prepared both in racemic and enantiomerically-pure form, with the final aim to address the role of chirality in the SR interaction. To isolate and characterize enantiomeric compounds, high-performance liquid chromatography (HPLC) procedures were set up. A systematic analytical screening, involving several combinations of chiral stationary and mobile phases, allowed us to optimize the analytical resolution and to set up the (semi-)preparative chromatographic conditions. Applying the optimized procedure, the enantiomeric resolution of the studied compounds was successfully achieved, obtaining all of the compounds with an enantiomeric excess higher than 95%. Lastly, the absolute configuration has been empirically assigned to enantiopure compounds, combining the electronic circular dichroism (ECD) technique to the elution order study.